THE CLIMATE CHANGE IMPACT ON THE GLACIERS OF GEORGIA - G. I. Kordzakhia; L. D. Shengelia; G. A. Tvauri; M. Sh. Dzadzamia (World Science, 2019)
The article reviews the changes of the glacier basins characteristics of Georgia glaciers due to the current climate change. Calculations show significant decrease of the area and number of the glaciers in Georgia over the last 50 years. This reduction is more intensive in eastern Georgia in comparison with the western part of the country. At the same time, some large glaciers complete melting dates are determined according to one of the basic scenarios of current climate change, namely the business as usual. Based on the calculations it is concluded that viewed large glaciers complete melting is not expected within this century even in this worst conditions scenario.